2021
DOI: 10.2147/amep.s342582
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Students and Examiners about Objective Structured Clinical Examination in a Teaching Hospital in Ethiopia

Abstract: Introduction The objective structured clinical examination (OSCE) has become a standard assessment tool in undergraduate medical school training. It is considered an objective assessment of practical skill of students. OSCE is a resource demanding assessment method that can have numerous challenges. Comprehensive assessment of perception regarding OSCE can help identify areas that need improvement. The aim of this study was to assess the perception of students and examiners towards OSCE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Furthermore, 62.3% of the participants believed that OSCE as an evaluation method covered a broad spectrum of critical areas. These findings are in line with the outcomes of previous studies, which showed that more than two-thirds of their participants perceived OSCE as a fair testing tool for knowledge, covered various clinical skills, and substantiated that OSCE meditates what students learn in their courses [6,17,42,43]. Thus, these studies' participants developed positive attributes [6,44] and favorable attitudes toward OSCE, i.e., the mean attitude score of participants toward OSCE was 85.71 with a standard deviation of 8.50 [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, 62.3% of the participants believed that OSCE as an evaluation method covered a broad spectrum of critical areas. These findings are in line with the outcomes of previous studies, which showed that more than two-thirds of their participants perceived OSCE as a fair testing tool for knowledge, covered various clinical skills, and substantiated that OSCE meditates what students learn in their courses [6,17,42,43]. Thus, these studies' participants developed positive attributes [6,44] and favorable attitudes toward OSCE, i.e., the mean attitude score of participants toward OSCE was 85.71 with a standard deviation of 8.50 [16].…”
Section: Discussionsupporting
confidence: 90%
“…Simultaneously, a continuous review of scenarios for each OSCE station should occur before actual clinical skills evaluation. As a result, the more OSCE assessment audit carried out, the more advanced the evaluation method of OSCE in an institution [31,42]. Hence, many educators consider OSCE as an effective evaluation method for practical clinical skills because of the significant benefits of OSCE over the disadvantages that it causes [31,49,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction among examiners and students have been highlighted as stressor by previous studies (Fisseha & Desalegn, 2021;Majumder et al, 2019) using indirect tools (surveys) to examine stress. According to our HRV results, this could explain the high stress response in the non-interactive written scenarios (S4 and S9) in which students do not interact with patients but only with examiners.…”
Section: Discussionmentioning
confidence: 99%
“…The increased stress response was also observed in physiotherapy students, where a high anticipatory anxiety response was evaluated at both, subjective and objective level, in clinical simulations, not achieving the expected habituation [13]. In this line, several studies based on students self-perception questionnaires, have reported the OSCE as an "anxiety provoking assessment method" due to scenarios timing, the proximity of the evaluator and the high expectation to succeed [7,19]. Academic events such as OSCE, practices and final degree defence confront the students with a potentially stressful and warning situation.…”
Section: Introductionmentioning
confidence: 90%